2005
DOI: 10.1016/j.virol.2005.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Genetic incorporation of HSV-1 thymidine kinase into the adenovirus protein IX for functional display on the virion

Abstract: Adenoviral vectors have been exploited for a wide range of gene therapy applications. Direct genetic modification of the adenovirus capsid proteins has been employed to achieve alteration of vector tropism. We have defined the carboxy-terminus of the minor capsid protein pIX as a locus capable of presenting incorporated ligands on the virus capsid surface. Thus, we sought to exploit the possibility of incorporating functional proteins at pIX. In our current study, we incorporated the herpes simplex virus type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
62
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 42 publications
6
62
0
Order By: Relevance
“…Besides its role as a structural protein, it is a transcriptional activator (Rosa-Calatrava et al, 2001;Sargent et al, 2004a) and reorganizes promyelocytic leukaemia (PML) nuclear bodies (Rosa-Calatrava et al, 2003) (reviewed by Parks, 2005). Protein IX has been extensively studied as a platform to express foreign peptides on the surface of the capsid (Dmitriev et al, 2002;Le et al, 2004;Li et al, 2005;Meulenbroek et al, 2004;Vellinga et al, 2004Vellinga et al, , 2007. Since protein IX has been so well characterized, we selected it as a fusion partner to test whether 2A sequences could be used to express foreign genes in adenoviruses.…”
Section: Introductionmentioning
confidence: 99%
“…Besides its role as a structural protein, it is a transcriptional activator (Rosa-Calatrava et al, 2001;Sargent et al, 2004a) and reorganizes promyelocytic leukaemia (PML) nuclear bodies (Rosa-Calatrava et al, 2003) (reviewed by Parks, 2005). Protein IX has been extensively studied as a platform to express foreign peptides on the surface of the capsid (Dmitriev et al, 2002;Le et al, 2004;Li et al, 2005;Meulenbroek et al, 2004;Vellinga et al, 2004Vellinga et al, , 2007. Since protein IX has been so well characterized, we selected it as a fusion partner to test whether 2A sequences could be used to express foreign genes in adenoviruses.…”
Section: Introductionmentioning
confidence: 99%
“…132,133 Further, other Ad vectors harboring complex ligands at the pIX locale have been reported. [134][135][136] As a whole, these studies have established pIX as a highly relevant capsid locale marked by the highest structural compatibility, with diverse targeting and imaging ligands observed to date.…”
Section: Adenovirus Targeting Via Genetic Modification: Other Capsidmentioning
confidence: 91%
“…For example, incorporation of genetically modified fibers, combined with imaging motifs on the pIX protein, could be used to simultaneously target tumor cells while monitoring viral replication and spread. In this regard, in addition to optical imaging-based ligands that have been incorporated at pIX as mentioned above, recently Li et al 136 have been successful in incorporating the enzyme Herpes Simplex Virus thymidine kinase (HSV-tk) at this capsid locale. This enzyme is compatible with available PET imaging ligands such as 18 F-penciclovir, providing an imaging system for viral replication that can directly be translated for clinical applications.…”
Section: Future Applicationsmentioning
confidence: 99%
“…To prove this concept, we determined that the minor capsid protein, pIX, would be a suitable anchorage position for the shielding molecule. This is due to the large body of work indicating that carboxy terminus of pIX can be fused to an array of molecules including polylysine [29], the biotin acceptor peptide (BAP) [30] and larger complex proteins including various fluorescent proteins, HSV thymidine kinase (TK) and TK fusions [31][32][33][34][35][36]. In these studies it was demonstrated that virus viability was not significantly affected and that the pIX-fused molecules retained functionality.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to using hALB directly fused to pIX we decided to utilize another self-protein, alpha-1-antitrypsin (A1A), in parallel for direct incorporation. Although it is not as large as hALB, A1A is of a comparable size to HSV-TK, which has been successfully fused to pIX in replicating Ad vectors [31]. A1A is a serine proteinase inhibtitor with a primary function to inhibit the enzyme neutrophil elastase.…”
Section: Introductionmentioning
confidence: 99%